Kentucky's natural heritage : a an illustrated guide to biodiversity - Abernathy, Greg (The University Press of Kentucky, 2010)
Photographs and text examine the species of plants and animals native to Kentucky, exploring glades, prairies, forests, wetlands, rivers, and caves, and discussing the state's conservation efforts to preserve native species and ecosystems.